The FRISBEE tool, a software for optimising the trade-off between food quality, energy use, and global warming impact of cold chains. (March 2015) - Gwanpua, S.G.; Verboven, P.; Leducq, D.; Brown, T.; Verlinden, B.E.; Bekele, E.; Aregawi, W.; Evans, J.; Foster, A.; Duret, S.; Hoang, H.M.; van der Sluis, S.; et al.
Highlights: A multi-disciplinary approach to assess cold chain sustainability was discussed. A software tool for quantifying cold chain sustainability was developed. Kinetic models for food quality were implemented in a user-friendly software. Abstract: Food quality (including safety) along the cold chain, energy use and global warming impact of refrigeration systems are three key aspects in assessing cold chain sustainability. In this paper, we present the framework of a dedicated software, the FRISBEE tool, for optimising quality of refrigerated food, energy use and the global warming impact of refrigeration technologies. The food quality models implemented in the FRISBEE tool are based on validated kinetic models, most of which are available as separate publications in this issue, while the models for calculating energy use and global warming impact have been validated using independent data. The software was developed within the framework of the European Union FP7 project, FRISBEE (Food Refrigeration Innovations for Safety, consumers' Benefit, Environmental impact and Energy optimisation along the cold chain in Europe). The consumers' version of the FRISBEE tool, with limited functionalities, will be made available as free downloadable software on the FRISBEE website, while the version with full functionalities will be used for consultancy.